NEW ECONOMIC POLICY IN 1991 AND CONSEQUENTLYVICISSITUDES IN TAMIL NADU - VENKATESH.R (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Abstract Politics and economics are ambiguous regarding the progress of a society. The economy can be considered a measure of social progress. A sustainable society under a stable state will lead to the collapse of an unstable regime that will not make sustainable progress. The political and economic changes that took place in India in the 1990s led to many changes. Tamil Nadu is the state that has used those changes to its advantage. This study illustrates some of those changes.